Chaotic Charged System Search with a Feasible-Based Method for Constraint Optimization Problems. (25th March 2013) - Nouhi, B.; Talatahari, S.; Kheiri, H.; Cattani, C.
Abstract : Recently developed chaotic charged system search was combined to feasible-based method to solve constraint engineering optimization problems. Using chaotic maps into the CSS increases the global search mobility for a better global optimization. In the present method, an improved feasible-based method is utilized to handle the constraints. Some constraint design examples are tested using the new chaotic-based methods, and the results are compared to recognize the most efficient and powerful algorithm.